Non-rotating and slowly rotating white dwarfs in classical physics (Physical Sciences and Technology, 2016)
The equilibrium configurations of uniformly rotating white dwarfs are calculated in the framework of classical physics. The Chandrasekhar and the Salpeter equations of state are used to describe the white dwarf matter. The Hartle formalism is applied to the integration of the equations of hydrostatic equilibrium and field equations. The equations of structure have been expanded in powers of the angular velocity Ω of the white dwarf, and terms of higher order than Ω
Keywords: Key words; white dwarfs; uniform rotation; Hartle’s formalism; equilibrium configurations; moment of inertia; quadrupole moment. PACS numbers; 97.10.Cv; 97.10.Kc; 97.10.Nf; 97.10.Pg; 97.20.Rp.